The Influence of Knowledge and Attitude Factors on Compliance with Drinking Oat (Anti-Tuberculosis Drugs) In Patients with Lung Tuberculosis in the Regional Public Hospital, dr. Husni Thamrin Natal Sumatera Utara - Safarianti Safarianti; Rolan Ronaldo; Rina Suryani Oktari (Budapest International Research in Exact Sciences (BirEx) Journal, 2021)
Pulmonary Tuberculosis (TB) is a lung infection caused by bacillus bacteria called Mycobacterium tuberculosis. MTB generally attacks the lungs and carries a very high risk of transmission. Patients with TB are potentially non-adherent totake anti-tuberculosis drugs (OAT) regularly as directed due to a long period of medication. Factors affecting ATD taking compliance include knowledge and attitudes of pulmonary TB patients. This study aimed to determine the relationship of knowledge and attitude of tuberculosis patients with compliance of ATD drinking in RSUD dr. Husni Thamrin Natal Regency Mandailing Natal. The research was conducted in dr. Husni Thamrin Natal. This research is an observational analytic by cross sectional design which involved 57 participants taken with consecutive sampling method. Data were processed into Spearman ' s correlation test. The result showed that knowledge (p value = 0,000) and attitude (p value = 0,000) related to OAT drinking compliance. This research had proven that the knowledge and attitudes affected OAT drinking compliance of the TB outpatient in RSUD dr. Husni Thamrin Natal, Mandailing Natal Regency.